Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1002/1097-0142(19910201)67:3<564::aid-cncr2820670306>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy for anaplastic giant cell thyroid carcinoma

Abstract: Since 1981, 20 patients with anaplastic giant cell carcinoma of the thyroid have been prospectively treated according to a combination regimen of chemotherapy and external beam radiation therapy. Two types of chemotherapy were used every 4 weeks, depending on the patient's age. For those younger than 65 years, a combination of doxorubicin (60 mg/m2) and cisplatin (90 mg/m2) was given, and for older patients mitoxantrone (14 mg/m2) was used. Radiotherapy was carried out between Day 10 and Day 20 of the first fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
51
1
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(54 citation statements)
references
References 8 publications
1
51
1
1
Order By: Relevance
“…No response was observed in distant metastases in the present study, nor in another study employing doxorubicin (60 mg m 2 ), cisplatin (90 mg m 2 ) and local radiation (Schlumberger et al, 1991). The use of a more aggressive cytostatic regimen in a multimodal approach is therefore not justified, except possibly in younger subjects in good performance upon termination of local therapy.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…No response was observed in distant metastases in the present study, nor in another study employing doxorubicin (60 mg m 2 ), cisplatin (90 mg m 2 ) and local radiation (Schlumberger et al, 1991). The use of a more aggressive cytostatic regimen in a multimodal approach is therefore not justified, except possibly in younger subjects in good performance upon termination of local therapy.…”
Section: Discussioncontrasting
confidence: 78%
“…Surgery, radiotherapy, or chemotherapy used alone is seldom sufficient to control the disease (Aldinger et al, 1978;Venkatesh et al, 1990), while a combination of these modalities may improve local control (Venkatesh et al, 1990;Schlumberger et al, 1991). The rationale for combining radio-and chemotherapy is that, as the toxicity of these modalities does not entirely overlap, an enhanced tumouricidal effect may be obtained (Wendt et al, 1985).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16] However, to our knowledge, few published data have shown any significant survival benefit from multimodal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with the reports which found no improvement in survival despite the combination of chemotherapy and radiotherapy, and which concluded that the role of chemotherapy, preoperatively or postoperatively is equivocal. 20,21 It has been acknowledged that the efficacy of radiotherapy for ATC is largely unsatisfactory, and in particular, conventional radiotherapy has not seemed to have any therapeutic effects at all. 19,22 Despite these disappointing results of conventional radiotherapy, hyperfractionated radiation therapy and combined chemotherapy has been suggested as a multimodal treatment approach to improve survival rates, 6,15,16 though some disagree.…”
Section: Discussionmentioning
confidence: 99%